CD4+CD25highCD127- regulatory T-cells in COPD: smoke and drugs effect. Issue 1 (December 2016) - Chiappori, Alessandra; Folli, Chiara; Balbi, Francesco; Caci, Emanuela; Riccio, Anna; De Ferrari, Laura; Melioli, Giovanni; Braido, Fulvio; Canonica, Giorgio
Abstract Background Chronic obstructive pulmonary disease (COPD) is a progressive lung disorder characterized by poorly reversible airway obstruction and its pathogenesis remains largely misunderstood. Local changes of regulatory T-cell populations in the lungs of COPD patients have been demonstrated although data concerning their pathologic role are contrasting. The aim of our study was to evaluate the relative percentage of regulatory T-cells in the peripheral blood of current and former smoker subjects, affected or not by COPD. Furthermore, the effect of different concentrations of budesonide and formoterol, on regulatory T-cells has been investigated. Methods T regulatory lymphocytes were isolated and assessed as CD4+ CD25high CD127- cells by flow cytometry and cultured for 48 hours in the absence or in the presence of budesonide and/or formoterol at different doses. Results CD4+ CD25high CD127- regulatory T-cells percentage was significantly reduced in COPD patients, both current and former smokers, with respect to volunteers. Furthermore, CD4+ CD25high CD127- cells of COPD patients showed a not statistically significant response to drugs compared to healthy subjects. Discussion Our results evidenced a different behaviour of CD4+ CD25high CD127- Treg cells in COPD patients after in vitro treatments. Conclusions Based on our data, we suggested a possible role of CD4 CD25high CD127 T-cells in COPD pathogenesis.